1998
DOI: 10.1542/peds.101.4.604
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of Heptavalent Pneumococcal Vaccine Conjugated to CRM197 in United States Infants

Abstract: Primary immunization followed by a booster dose of PNCRM7 seemed to be acceptably safe and resulted in significant rises in antibody to all 7 serotypes. Implications. Studies to assess vaccine efficacy of PNCRM7 for prevention of systemic disease, nasopharyngeal colonization, and acute otitis media are in progress. If PNCRM7 proves to be protective, there is the potential to prevent up to 85% of invasive pneumococcal disease occurring in US children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
173
4
9

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 358 publications
(200 citation statements)
references
References 19 publications
12
173
4
9
Order By: Relevance
“…Moreover these conjugate vaccines will induce a memory response with a rise of antibody titer after several rounds of Table 1 Box 1 immunization and a booster response several months later . Surprisingly, in older infants and in adults, the same conjugate vaccine [21][22][23][24] does not induce a memory response but a response similar to the one obtained with the plain CPS preparation , even though the [25][26][27][28] response to the conjugate appears in some cases more robust . We have shown that humans display a circulating marginal zone B cell population which is involved in TI response and which diversifies its Ig receptor in the absence of cognate T-B interactions.…”
Section: Paradoxmentioning
confidence: 99%
“…Moreover these conjugate vaccines will induce a memory response with a rise of antibody titer after several rounds of Table 1 Box 1 immunization and a booster response several months later . Surprisingly, in older infants and in adults, the same conjugate vaccine [21][22][23][24] does not induce a memory response but a response similar to the one obtained with the plain CPS preparation , even though the [25][26][27][28] response to the conjugate appears in some cases more robust . We have shown that humans display a circulating marginal zone B cell population which is involved in TI response and which diversifies its Ig receptor in the absence of cognate T-B interactions.…”
Section: Paradoxmentioning
confidence: 99%
“…Foi avaliada a ocorrência de doenças invasivas produzidas a partir de 14 dias após o término das três primeiras doses, que se mostrou muito alta 89,90,15 (Tabela 2).…”
Section: Vacinas Antipneumocócicasunclassified
“…Large studies have shown that a pneumococcal conjugate vaccine is immunogenic and reduces invasive disease in infants and children. [33][34][35] …”
Section: Discussionmentioning
confidence: 99%